1997
DOI: 10.1161/01.hyp.29.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Blood Pressure Fall on Ambulatory Monitoring in a Large International Database

Abstract: A wide range of definitions is used to distinguish subjects in whom blood pressure (BP) falls at night (dippers) from their counterparts (nondippers). In an attempt to standardize the definition of nondipping, we determined the nocturnal BP fall and night-day BP ratio by 24-hour ambulatory monitoring in 4765 normotensive and 2555 hypertensive subjects from 10 to 99 years old. In all subjects combined, the systolic/diastolic nocturnal fall and corresponding ratio averaged (+/- SD) -16.7 +/- 11.0/ -13.6 +/- 8.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
186
2
19

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(216 citation statements)
references
References 44 publications
(4 reference statements)
9
186
2
19
Order By: Relevance
“…The cutoff values of day-night difference in BP that we found to be more appropriate for identifying patients with autonomic neuropathy, approximate to the 95th percentile of the distribution of day-night variation in BP in a large international database in normotensive subjects. 20 Moreover, Hansen et al 32 found that in 137 normoalbuminuric normotensive adult type I diabetic patients, the 95th percentile level of the daynight difference in SBP and DBP were 3 and 6%, respectively, which as values are rather similar to those identified by us as appropriate diagnostic cutoff points for autonomic neuropathy (i.e. 0 and 5%).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The cutoff values of day-night difference in BP that we found to be more appropriate for identifying patients with autonomic neuropathy, approximate to the 95th percentile of the distribution of day-night variation in BP in a large international database in normotensive subjects. 20 Moreover, Hansen et al 32 found that in 137 normoalbuminuric normotensive adult type I diabetic patients, the 95th percentile level of the daynight difference in SBP and DBP were 3 and 6%, respectively, which as values are rather similar to those identified by us as appropriate diagnostic cutoff points for autonomic neuropathy (i.e. 0 and 5%).…”
Section: Discussionsupporting
confidence: 56%
“…In a multiple logistic regression after adjustment for the clinical correlates known to affect nocturnal BP fall in the general population, 20 that is sex, age, and body mass index, the odds ratio for having autonomic neuropathy was seven times higher in Nondipping as diagnostic tool for autonomic neuropathy V Spallone et al systolic nondippers as opposed to systolic dippers (odds ratio 6.97, 95% CI 1.4-34.9, P ¼ 0.018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-dipping status was defined as a night-time/daytime SBP or DBP ratio X100%. 22 Biochemical measurements Plasma glucose, cholesterol, triglycerides and uric acid concentrations were measured on an automated analyser (Roche Diagnostics, Mannheim, Germany). Serum insulin was measured in duplicate by a chemiluminescent assay (DPC, Los Angeles, CA, USA; sensitivity 14.3 pmol l À1 and intra-and interassay coefficients of variation (CVs) 3.7 and 6.7%, respectively).…”
Section: Blood Pressure Measurementsmentioning
confidence: 99%
“…12 multiplied by 100 to express the night-time BP as a percentage of the mean daytime SBP, DBP and Subjects with a history of elevated BP were categorized as borderline hypertensive if the average sys-MAP. 16 Cusums and cusum-derived statistics were calculated as described elsewhere. 17 Briefly, this tolic or diastolic BP on at least three separate occasions within 3 months of the monitoring period method involves subtracting the time-weighted mean 24-h BP from each successive BP measurewas between the 90th and 95th percentiles for age and gender or as having hypertension if above the ment, adding these deviations adjusted for the length of the preceding time interval and plotting 95th percentile.…”
Section: Introductionmentioning
confidence: 99%